Dampak Pemanfaatan Media dan Metode Pembelajaran terhadap Keaktifan Siswa dalam Pembelajaran Pendidikan Pancasila di SDN Jatisari - Almayra naura; Ammara Meysha Laksmi; Susilo Tri Widodo; Titania Kharisa Nurul (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the impact of learning media utilization and the implementation of Inquiry-Based Learning (IBL) and Project-Based Learning (PjBL) models on student engagement in Pancasila Education at SDN Jatisari. The research was motivated by the low level of student participation observed during initial classroom activities, which was influenced by unequal learning facilities and the teacher’s limited use of varied teaching methods.. Data were collected through direct observations, informal interviews with the classroom teacher, and documentation. The findings reveal that prior to the intervention, students tended to be passive, less attentive, and minimally involved in discussions. Following the implementation of IBL and PjBL supported by simple visual media, students demonstrated significant improvement in engagement, indicated by increased participation in discussions, active questioning, collaborative group work, and enhanced motivation. These results confirm that appropriate learning media combined with interactive and student-centered learning models effectively increase student engagement in Pancasila Education at the primary level.